Rapid Serial Visual Presentation Design for Cognition - Spence, Robert; Witkowski, Mark.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
A powerful new image presentation technique has evolved over the last twenty years, and its value demonstrated through its support of many and varied common tasks. Conceptually, Rapid Serial Visual Presentation (RSVP) is basically simple, exemplified in the physical world by the rapid riffling of the pages of a book in order to locate a known image. Advances in computation and graphics processing allow RSVP to be applied flexibly and effectively to a huge variety of common tasks such as window shopping, video fast-forward and rewind, TV channel selection and product browsing. At its heart is a remarkable feature of the human visual processing system known as pre-attentive processing, one which supports the recognition of a known image within as little as one hundred milliseconds and without conscious cognitive effort. Knowledge of pre-attentive processing, together with extensive empirical evidence concerning RSVP, has allowed the authors to provide useful guidance to interaction designers wishing to explore the relevance of RSVP to an application, guidance which is supported by a variety of illustrative examples.
Preface -- Acknowledgements -- What is RSVP? And why do I need it? -- Experimental Evidence -- RSVP Modes and their Properties -- Eye-gaze -- Analysing Gaze for RSVP -- Design -- Bibliography -- Index.
Keywords: Computer science; Architectural design; Visualization; Consciousness; Computer Science; User Interfaces and Human Computer Interaction; Computer Applications; Visualization; Cognitive Psychology; Interaction Design